Binge Eating Disorder and Fatphobia: Social Stigma, Exclusion, and the Need for a New Perspective on Health - Alexandra Ainz-Galende; María José Torres-Haro; Rubén Rodríguez-Puertas (Societies)
Binge eating disorder (BED) has long been an overlooked mental health condition, making its recognition and treatment more challenging. This study examines the impacts of social stigma and fatphobia on individuals with BED, exploring how these factors influence their well-being and perpetuate cycles of exclusion and discrimination. Using a psychosocial approach, this research analyzes how societal misperceptions about BED foster harmful stereotypes, such as the belief that being overweight results from a lack of willpower or personal negligence. This study is based on a qualitative discourse analysis of 12 participants diagnosed with BED. The findings highlight the presence of compensatory behaviors, including fasting, excessive exercise, and laxative use, which challenge the conventional understanding of BED. The results reveal that BED affects not only individuals at a personal level, but also deeply impacts their social and family lives, reinforcing shame, guilt, and self-hatred. Diet culture and weight stigma contribute to social exclusion, further hindering access to proper treatment. This study provides a critical perspective on the need for a cultural shift in how society perceives weight and eating behaviors, advocating for a more inclusive health model that prioritizes mental well-being and body diversity over arbitrary aesthetic standards. These findings underscore the need for greater societal understanding, inclusive health narratives, and further qualitative research into the lived experiences of individuals with BED.